2009
DOI: 10.1098/rspb.2009.1607
|View full text |Cite
|
Sign up to set email alerts
|

Are fast explorers slow reactors? Linking personality type and anti-predator behaviour

Abstract: Response delays to predator attack may be adaptive, suggesting that latency to respond does not always reflect predator detection time, but can be a decision based on starvation-predation risk trade-offs. In birds, some anti-predator behaviours have been shown to be correlated with personality traits such as activity level and exploration. Here, we tested for a correlation between exploration behaviour and response latency time to a simulated fish predator attack in a fish species, juvenile convict cichlids (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
117
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(132 citation statements)
references
References 49 publications
12
117
1
2
Order By: Relevance
“…However, exploration and antipredatory behavior were positively related among urban birds, but not among their rural counterparts. Exploration and fear of humans have been shown to be positively correlated in domestic red junglefowls (Agnvall et al, 2012), although studies relating exploration and antipredator behavior yielded inconclusive results (Jones and Godin, 2010;Couchoux and Cresswell, 2011). Explorative behaviors can be advantageous when invading novel habitats such as urban areas (Martin and Fitzgerald, 2005), neophilic/explorative phenotypes having advantages in exploiting novel food resources or food available in novel contexts (Tryjanowski et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, exploration and antipredatory behavior were positively related among urban birds, but not among their rural counterparts. Exploration and fear of humans have been shown to be positively correlated in domestic red junglefowls (Agnvall et al, 2012), although studies relating exploration and antipredator behavior yielded inconclusive results (Jones and Godin, 2010;Couchoux and Cresswell, 2011). Explorative behaviors can be advantageous when invading novel habitats such as urban areas (Martin and Fitzgerald, 2005), neophilic/explorative phenotypes having advantages in exploiting novel food resources or food available in novel contexts (Tryjanowski et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, prey that are attacked when close to a refuge exhibit a smaller reaction distance (Ydenberg and Dill, 1986). In fish, Jones and Godin described a trade-off between escape performance and exploratory foraging behaviour, where fast escape reactors were slower explorers and vice versa (Jones and Godin, 2010). Trade-offs may also exist between the burst performance used in the escape response and other types of swimming.…”
Section: The Standing Variation Does Not Reflect Trade-offs Amongst Tmentioning
confidence: 99%
“…There is a growing interest in investigating phenotypic variation in quantitative performance traits such as the escape response (Oufiero and Garland, 2009;Jones and Godin, 2010) because this may provide insight into their ecological or evolutionary significance. To have such significance, it is essential to demonstrate that individual variation in the trait is temporally stable and therefore an intrinsic, potentially life-long, characteristic of the individual (Oufiero and Garland, 2009), and thus subject to natural selection (Arnold, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…According to Barber and Dingemanse (Barber and Dingemanse, 2010), behaviours that are altered following infection with 'manipulative' parasites often correspond to major personality axes in behavioural studies. Indeed, considerations about animal personality have often revolved around the shy-bold continuum, which is of particular relevance to inter-individual variation in antipredator behaviour (Pellegrini et al, 2010;Jones and Godin, 2010). In parallel, several studies have shown that hosts infected with parasites with complex life cycles often show marked alterations of their anti-predatory behaviour (Libersat and Moore, 2000;Perrot-Minnot et al, 2007;Kaldonski et al, 2007).…”
Section: A Proximate View On Multidimensionality In Pipasmentioning
confidence: 99%